A Review of the Anaerobic Digestion Process - Ong, H.K.; Greenfield, P.F.; Pullammanapalul, P. (INTI Publishing House Sdn. Bhd., 2006)
As one of the oldest biological waste treatment processes, anaerobic digestion offers the advantages of low energy requirement, high treatment efficiency, low excess sludge production, low nutrient requirement, no oxygen requirement and energy recovery. This paper reviews the process covering its fundamental requirements, factors affecting it, effect of mixing as well as mixing regimes. The fundamental stage-wise processes of hydrolysis, acidogenesis, acetogenesis and methanogenesis were described. The factors affecting the performance of anaerobic digesters Include feeding rate, feeding mode (retention time), temperature, pH and alkalinity, nutrient content, toxicity, mixing frequency and intensity as well as the method of mixing. The factors affecting mixing in digesters are in turn reviewed in considerable detail. The relevance of anaerobic digestion in the light of the enforcement of the Kyoto Protocol was also discussed, together with the rationale for waste treatment options for minimization of greenhouse gases. It is concluded that treatment options for waste management should include anaerobic digestion in which methane ¡s captured for power generation, a planned process flow to minimize pumping of wastewater, planned bio solid flow to minimize internal transport and systems that avoid incineration using fossil fuel. Finally, more recent developments in the areas of microbial fuel cell as well as biological production of hydrogen were discussed. With the emergence of “white biotechnology” leading to the pursuit of bio- refinery projects, it is suggested that anaerobic digestion should now be integrated with bio-refinery activities to find its exclusive niches.